Estudo opto-mecânico de membranas suspensas de grafeno em uma plataforma microfluída - Gustavo Arrighi Ferrari (2018)
This thesis presents mechanical and optical studies of suspended graphene membranes on microfluidic devices that have an architecture named Platform. The Platform architecture allows the integration of suspended graphene membranes with fluids/liquids in a nonconventional way: the fluid/liquid touches the graphene from below, through the windows of suspended graphene. Consequently, there is no substrate supporting the graphene in the study of graphene-liquid interface like some other works in the literature. The integration of the suspended graphene membranes with the fluids/liquids is made by microfluidic channels buried in the substrate. The mechanical studies were performed by scanning probe microscopy techniques: atomic force microscopy, force spectroscopy and PeakForce QNM; and the optical ones were performed via Raman spectroscopy. Both graphene and the Platforms were synthesized/ fabricated at UFMG as part of this thesis, the former by chemical vapor deposition and the latter by various steps of clean room processing. The main objective of the optical-mechanical studies was to evaluate the behavior of the graphene mechanical properties when in contact with different fluids/liquids. This objective was successfully achieved by observing an apparent softening of the graphene membranes when the medium in the microfluidic buried channel changes from air to water. Nevertheless, a phenomenological model and molecular dynamic simulations demonstrated that this apparent softening of graphene is, actually, an uncrumpling/unwrinkling process of the last (induced by the water in the channel) and that, in fact the graphene Young modulus remains unchanged. By testing a fluid/liquid with a different surface tension, as the oleic acid, the results indicate a similar behavior for the graphene Young modulus (it remains unchanged), however, instead of softening, the studied graphene membrane shows apparent hardening. Presently, a model is being developed to explain this phenomenology. Finally, Raman spectroscopy results indicate a reversible behavior of D band and a condition of breaking suspended graphene membranes when illuminated with visible laser light and in contact with water.